Technological potential of native lactic acid bacteria isolated from Swiss-type artisanal cheese (Ancash, Peru) for their application in food - Valdiviezo-Marcelo, Jaime; Arana-Torres, Nancy Maribel; Vega-Portalatino, Edwin Jorge; Ruiz-Flores, Luis Alberto; Tamariz-Angeles, Carmen; Olivera-Gonzales, Percy; Rosales-Cuentas, Miriam Marleni; Espinoza-Espinoza, Luis Alfredo (Frontiers in Sustainable Food Systems, 2023)
Swiss-type artisanal cheese is highly valued sensorially, its flavor is often associated with the lactic acid bacteria involved in its production, which in many cases are indigenous. The objective of this study was to isolate, characterize and identify lactic acid bacteria of industrial interest from three Swiss-type artisanal cheeses. Eleven strains, Gram positive and catalase negative, were selected to be characterized from a nutritional point of view. According to 16S rDNA, seven strains belonged to Lacticaseibacillus paracasei (KQ3, EQ1, CQ1, YQ1, LQ2, GQ2 and TQ1), three strains to Lentilactobacillus parabuchneri (BQ2, OQ2 and RQ3), and one to Lactiplantibacillus sp. (QQ3). In safety trials, LAB did not present gelatinase or hemolytic activities. Besides, L. paracasei KQ3, GQ2 and L. parabuchneri BQ2 effectively inhibited pathogens such as S. aureus, E. coli and L. monocytogenes. Susceptibility to antibiotics was variable among the strains. All LAB strains were evaluated for their relevance in food application. In acidification, L. paracasei CQ1, EQ1, KQ3, TQ1 and Lactiplantibacillus sp. QQ3 showed a high milk acidification capacity (0.16 -1.44) and reduced the pH from 6.6 to 3.5 after 72 h of incubation. In proteolysis, L. paracasei CQ1, Lactiplantibacillus sp. QQ3 and L. paracasei KQ3 presented the largest casein degradation zones (20.8 -11.5 mm). All strains showed lipolytic activity, highlighting Lactiplantibacillus sp. QQ3, L. paracasei CQ1 and L. parabuchneri BQ2 with halos of 30.8-36.3 mm. Lactiplantibacillus sp. QQ3 and L. paracasei TQ1 showed the ability to produce diacetyl. The best strains were tested in the production of cheeses in which L. paracasei CQ1 showed the best sensory qualities. Finally, the native LAB isolates showed high biotechnological potential for the production of natural, safe and sensorially acceptable dairy products.